아스파라거스 부위별 유효성분 및 생리활성 분석 - 권순배(Soon-Bae Kwon); 권혜정(Hye-Jeong Kwon); 전신재(Shin-Jae Jeon); 서현택(Hyun-Taek Seo); 김희연(Hee-Yeon Kim); 임재길(Jae-Gil Lim); 박지선(Ji-Seon Park) (Han'guk Sikp'um Kwahakhoe Chi = Korean Journal of Food Science and Technology, 2020)
In this study, various constituents and biological activities of different parts of asparagus were analyzed and compared. The Ca content was high in the leaves, K was significantly high in the top 25 cm of the spear, and Fe and Na were significantly high in the roots. The ascorbic acid, rutin, total polyphenol, and total flavonoid contents were high in the leaves, and the asparagine and glutathione contents were significantly high in the top 25 cm of the spear and roots, respectively. The bottom 5 cm of the spear had the highest saponin content compared with all other parts. The DPPH and ABTS radical scavenging activities were the highest in the leaves. The bottom 5 cm of the spear had the highest αamylase inhibitory activity, whereas the stem showed the highest anti-inflammatory activity. These results suggest that the usually inedible parts of asparagus may be highly valuable as high-quality functional components owing to their antioxidative and anti-inflammatory activities.